Traumatic reticuloperitonitis in cattle: A clinical study - S.REDDY, Bhavanam; Reddy, L.S.S.Varaprasad; Sivajothi, S.; Reddy, B. Somasekhara (International Journal of Scientific World, 2014)
A cow with history of fever, anorexia, sudden milk drop and stiff gait was referred to the Teaching Veterinary Clinical Complex, College of Veterinary Science; Proddatur. Examination of the cow revealed fever, tachycardia, tachypnoea, with ruminal atony associated with mild bloat and dehydration was noticed. The cow exhibited light pain while palpation at brisket region. Hot and pain full edema was noticed at brisket region and at ventral abdomen. Animal exhibited positive response to metal detector. Haematology revealed significant erythrocytopenia, higher PCV, lower haemoglobin concentration, significant leucocytosis with neutrophilia, presence of more number of immature neutrophils and decreased lymphocyte count. Sero biochemical findings had reduced glucose, sodium, potassium, chloride, calcium, phosphorus levels and increased levels of total protein, globulin, AST, ALT, creatinine was noticed. Cow was treated with Inj. strepto penicillin, Inj.neoprofen along with supportive therapy. Keywords: Traumatic Reticuloperitonitis, Signs, Laboratory Findings, Cattle.